EMOTALK LIBRARY: LITERASI AFEKTIF BERBASIS DIGITAL UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL GENERASI MUDA - Muhammad Arif Fur'qon (El-Ihsan: Journal of Contemporary Islamic Education, 2026)
In the digital era, young people are exposed to rapid information flows, social media pressures, and phenomena such as toxic positivity and cancel culture, which challenge their emotional regulation and social interactions. This study aims to explore affective literacy needs among youth and conceptualize a digital platform, Emotalk Library, to support emotional understanding, self-reflection, and empathy. A qualitative Research and Development approach using a conceptual framework based on the Analysis, Design, and Development stages of the ADDIE model was employed. Data were collected through a comprehensive literature review of national and international journals, books, and academic publications related to affective literacy, digital literacy, and character education. The findings indicate that affective literacy is essential for developing emotional intelligence, resilience, and reflective behaviors. Emotalk Library features, including Emotion-Based Reading, Emotion Journal, EmoChatroom, and Emotalk Voice, are designed to address these needs and enhance affective skills in a structured digital environment. The study concludes that integrating affective literacy with digital literacy and character education is crucial for preparing youth to act wisely, empathetically, and adaptively in digital contexts. The conceptual framework provides a foundation for practical implementation and future research.